Le principe d’inertie et le conatus du corps - Épaminondas Vamboulis (Astérion)
The principle of inertia, despite the fact that it cannot be proven by any kind of experimental observation, is one of those principles that during the seventeenth century formed the foundations of a new physics. Both Descartes and Spinoza have tried however to demonstrate this principle and integrate it in their philosophical systems. Spinoza even proposes in his work Descartes’ Principles of Philosophy, while presenting Descartes’ view on that matter, a critical appraisal of some of the metaphysical presuppositions of the cartesian demonstration. An analysis of Spinoza’s arguments leads us to a study of the relation of the principle of inertia and the conatus theory of the Ethics, and subsequently to an interrogation concerning the status of Spinoza’s physics and the place that this science occupies in Spinoza’s philosophy.